The functional role of sibling aggression and "best of a bad job" strategies in cichlid juveniles. (5th April 2021) - Satoh, Shun; Nishida, Yuusuke; Saeki, Taiga; Kawasaka, Kento; Kohda, Masanori; Awata, Satoshi
Abstract: Siblings often compete for limited resources, such as food provided by their parents. However, although several functions of nonlethal sibling (nonsiblicidal) aggression have been proposed, there is currently little empirical evidence for these, apart from food monopolization. Here, we investigated the functions of nonlethal sibling aggression in the biparental-caring territorial herbivorous cichlid Varibilichromis moorii . We found that the juveniles of this species are highly aggressive and that larger juveniles are more aggressive toward their smaller siblings. Larger juveniles feed on algae more frequently than smaller siblings, thereby indicating a dominance hierarchy. Sibling aggression decreased when algae in the nest was experimentally removed. Furthermore, the removal of smaller juveniles decreased sibling aggression among the remaining larger juveniles, whereas the removal of larger juveniles increased aggression among smaller juveniles. The algal feeding rate of juveniles only increased when larger individuals were removed from the nest. Moreover, larger juveniles attained higher growth rates and remained in natal nests longer than smaller individuals. Our results indicate that sibling aggression may facilitate the monopolization of resources by larger juveniles and extend the parental care period. Interestingly, a small subset of juveniles was observed to migrate to other nests. These juveniles were larger than those of the host brood, and their growth rate increased within the new nests. We suggest that subordinate juveniles may disperse from natal nests and sneak into new nests to enhance their rank, which may represent a novel example of a "best of a bad job" strategy associated with sibling competition. Abstract : Sibling conflict is a key issue in behavioral ecology, yet little is known of the fitness benefits in species with nonlethal sibling aggression. We show that nonlethal sibling aggression aids the monopolization of food in parental nests and extends the parental care period in a cichlid fish. Some fry migrate from their natal nests to other nests, increasing their dominance rank as a "best of a bad job" strategy for siblings low in the dominance hierarchy.